Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

By using composite particles composed of amorphous carbonaceous particles and silicon particles as the negative electrode material of lithium-ion secondary batteries, the problem of insufficient circulation characteristics and insufficient discharge capacity in the prior art is solved, and the further development is achieved Excellent battery performance.

CN119404328APending Publication Date: 2025-02-07TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046382.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, although the composite particles formed by composited silicon particles and carbonaceous materials can improve the circulation characteristics of lithium-ion secondary batteries, there are still problems such as insufficient circulation characteristics and insufficient discharge capacity.

Method used

The composite particles formed by combining amorphous carbonaceous particles and silicon particles are used as the negative electrode material of the lithium-ion secondary battery, and specifically includes the first composite particles and the second composite particles. By adjusting the proportion and particle size of the composite particles, Optimize the structure of the negative electrode active material layer.

Benefits of technology

The circulation characteristics and discharge capacity of lithium-ion secondary batteries are significantly improved, and the negative impact of volume expansion of negative electrode active substances on battery performance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404328A_ABST
    Figure CN119404328A_ABST
Patent Text Reader

Abstract

This negative electrode material for lithium ion secondary batteries contains composite particles obtained by compounding amorphous carbonaceous particles and amorphous silicon particles. The silicon particles have an average primary particle diameter of 1 nm or more and 50 nm or less. The composite particles include first composite particles having a silicon content of 0.5 wt% to 5 wt% and second composite particles having a silicon content of 60 wt% to 70 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery and a lithium ion secondary battery. Background Art

[0002] Lithium-ion secondary batteries are also widely used as a power source for mobile devices such as mobile phones and laptop computers, and hybrid vehicles.

[0003] The capacity of lithium-ion secondary batteries depends mainly on the active material of the electrode. Graphite is generally used as the negative electrode active material, but a higher capacity negative electrode active material is required. Therefore, silicon (Si), which has a theoretical capacity far greater than that of graphite (372 mAh / g), has attracted much attention.

[0004] The negative electrode active material containing silicon is accompanied by a large volume expansion during charging. The volume expansion of the negative electrode active material becomes the reason for the reduction of the cycle characteristics of the battery. If the volume expansion of the negative electrode active material occurs, for example, the negative electrode active material is damaged, or the conductive path between the negative electrode active materials is cut off, or peeling occurs at the interface between the negative electrode active material layer and the collector, or cracks are generated in the SEI (Solid Electrolyte Interphase) film and the electrolyte decomposition occurs. These reduce the cycle characteristics of the battery.

[0005] For example, in order to improve the cycle characteristics of batteries, composite particles formed by combining silicon particles and carbonaceous materials are described in Patent Documents 1 to 3. Patent Documents 1 to 3 describe methods for combining silicon particles and carbonaceous materials, such as a mechanochemical method and a mixing heating method.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 4379971

[0009] Patent Document 2: Japanese Patent No. 3995050

[0010] Patent Document 3: Japanese Patent Application Publication No. 2008-277232 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] When composite particles formed by combining silicon particles and carbonaceous materials are used, the cycle characteristics are improved. On the other hand, even when composite particles are used, there are cases where the cycle characteristics cannot be sufficiently improved and where sufficient discharge capacity cannot be obtained. For example, if the mechanochemical method described in Patent Document 1 is used for composite, when compressive force and cutting force are applied to the carbon material and the silicon compound, sometimes part of the silicon compound is converted into silicon carbide. Silicon carbide also has little help in charging and discharging among silicon compounds, and sometimes the negative electrode active material cannot show sufficient capacity.

[0013] The present disclosure has been made in view of the above-mentioned problems, and an object of the present disclosure is to provide a lithium ion secondary battery having excellent cycle characteristics.

[0014] Technical solutions for solving technical problems

[0015] In order to solve the above-mentioned problems, the following technical solutions are provided.

[0016] (1) The negative electrode material for lithium ion secondary battery involved in the first embodiment contains composite particles formed by a composite of amorphous carbonaceous particles and amorphous silicon particles. The average primary particle size of the silicon particles is 1 nm or more and 50 nm or less. The composite particles include first composite particles with a silicon content of 0.5% by weight or more and 5% by weight or less and second composite particles with a silicon content of 60% by weight or more and 70% by weight or less.

[0017] (2) In the negative electrode material for a lithium ion secondary battery of the above aspect, the ratio of the first composite particles may be 3% by volume to 40% by volume, and the ratio of the second composite particles may be 1% by volume to 20% by volume.

[0018] (3) In the negative electrode material for a lithium ion secondary battery of the above aspect, the ratio of the first composite particles may be 6 volume % to 30 volume % and the ratio of the second composite particles may be 2 volume % to 15 volume %.

[0019] (4) In the negative electrode material for a lithium ion secondary battery of the above aspect, the average secondary particle size of the composite particles may be 3 μm or more and 10 μm or less.

[0020] (5) In the negative electrode material for lithium ion secondary battery of the above aspect, the specific surface area may be 3 m 2 / g above 25m 2 / g or less.

[0021] (6) A negative electrode for a lithium ion secondary battery according to a second aspect includes the negative electrode material for a lithium ion secondary battery of the above aspect.

[0022] (7) A lithium ion secondary battery according to a third aspect includes the negative electrode for a lithium ion secondary battery of the above aspect, a positive electrode, and an electrolyte connecting the positive electrode and the negative electrode for a lithium ion secondary battery.

[0023] Effects of the Invention

[0024] The lithium ion secondary battery of the above embodiment is excellent in cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic cross-sectional view of the lithium ion secondary battery according to the first embodiment.

[0026] Figure 2 This is a picture of a cross section of the negative electrode active material layer of the first embodiment taken with a scanning electron microscope (SEM).

[0027] Figure 3 It is a schematic diagram of composite particles contained in the negative electrode active material layer of the first embodiment. DETAILED DESCRIPTION

[0028] Below, with appropriate reference Figure 1 The embodiments are described in detail. In order to facilitate the understanding of the features, the drawings used in the following description sometimes enlarge the features for convenience, and sometimes the dimensional ratios of the components are different from the actual ones. The materials, dimensions, etc. exemplified in the following description are examples, and the present disclosure is not limited to these, and can be appropriately changed and implemented within the scope of not changing its purpose.

[0029] "Lithium-ion secondary battery"

[0030] Figure 1 It is a schematic diagram of the lithium ion secondary battery of the first embodiment. Figure 1 The lithium-ion secondary battery 100 shown in the figure includes a power generation element 40, a package 50, and an electrolyte (for example, a non-aqueous electrolyte). The package 50 surrounds the power generation element 40. The power generation element 40 is connected to the outside by a pair of terminals 60 and 62 connected to the power generation element 40. The non-aqueous electrolyte is contained in the package 50. Figure 1 In the embodiment, a case where one power generating element 40 is included in the package 50 is exemplified, but a plurality of power generating elements 40 may be stacked.

[0031] (Power generation element)

[0032] The power-generating element 40 includes a separator 10, a positive electrode 20, and a negative electrode 30. The power-generating element 40 may be a stacked body in which these are stacked, or a wound body in which these stacked structures are wound.

[0033] <Positive electrode>

[0034] The positive electrode 20 includes, for example, a positive electrode current collector 22 and a positive electrode active material layer 24 . The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode current collector 22 .

[0035] [Positive electrode collector]

[0036] The positive electrode current collector 22 is, for example, a conductive plate. The positive electrode current collector 22 is, for example, a thin metal plate such as aluminum, copper, nickel, titanium, or stainless steel. Lightweight aluminum is suitable for the positive electrode current collector 22. The average thickness of the positive electrode current collector 22 is, for example, not less than 10 μm and not more than 30 μm.

[0037] [Positive electrode active material layer]

[0038] The positive electrode active material layer 24 contains, for example, a positive electrode active material. The positive electrode active material layer 24 may contain a conductive auxiliary agent and a binder as necessary.

[0039] The positive electrode active material includes an electrode active material capable of reversibly absorbing and releasing lithium ions, desorbing and inserting (intercalating) lithium ions, or doping and dedoping lithium ions and counter anions.

[0040] The positive electrode active material is, for example, a composite metal oxide. The composite metal oxide is, for example, an oxide mainly containing a transition metal element and lithium. The transition metal element is, for example, Ti, V, Cr, Mn, Fe, Co, Ni, Mo, W, preferably V, Cr, Mn, Fe, Co, Ni. The molar ratio of lithium to the transition metal element (lithium / transition metal element) is, for example, 0.3 or more and 2.2 or less.

[0041] The positive electrode active material may contain Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, B, etc. in a range of 30 mol % or less relative to the transition metal element. The positive electrode active material is preferably, for example, a material having the general formula Li y MO2 (M is at least one of Co, Ni, Fe, Mn, 0≤y≤1.2), or Li z Materials having a spinel structure represented by N2O4 (N contains at least Mn. 0≤z≤2), etc.

[0042] The positive electrode active material is, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), and the general formula: LiNi x Co y Mn z M aO2 compounds (in the general formula, x+y+z+a=1, 0≤x<1, 0≤y<1, 0≤z<1, 0≤a<1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compounds (LiV2O5), olivine-type LiMPO4 (wherein M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 )、LiNi x Co y Al z O2 (0.9<x+y+z<1.1). The positive electrode active material may also be an organic substance. For example, the positive electrode active material may also be polyacetylene, polyaniline, polypyrrole, polythiophene, or polyacene.

[0043] The positive electrode active material may also be a material that does not contain lithium. The material that does not contain lithium is, for example, FeF3, a conjugated polymer containing an organic conductive material, a Chevreul phase compound, a transition metal chalcogenide, a vanadium oxide, a niobium oxide, and the like. The material that does not contain lithium may be any one material alone, or a combination of multiple materials may be used. In the case where the positive electrode active material is a material that does not contain lithium, for example, discharge is first performed. Lithium is inserted into the positive electrode active material by discharge. In addition, the positive electrode active material may be chemically or electrochemically pre-doped with lithium as a material that does not contain lithium.

[0044] The conductive additive improves the electronic conductivity between the positive electrode active materials. The conductive additive is, for example, carbon powder, carbon nanotubes, carbon materials, metal powder, a mixture of carbon materials and metal powder, and conductive oxides. Carbon powder is, for example, carbon black, acetylene black, Ketjen black, etc. Metal powder is, for example, powder of copper, nickel, stainless steel, iron, etc.

[0045] The binder in the positive electrode active material layer 24 binds the positive electrode active materials to each other. The binder can use a known binder. Preferably, the binder is insoluble in the electrolyte, has oxidation resistance, and has adhesiveness. The binder is, for example, a fluororesin. The binder is, for example, polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyether sulfone (PES), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polytrifluorochloroethylene (PCTFE), ethylene-trifluorochloroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), etc.

[0046] The adhesive may also be fluororubber. For example, the adhesive may be vinylidene fluoride-hexafluoropropylene fluororubber (VDF-HFP fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene fluororubber (VDF-HFPTFE fluororubber), vinylidene fluoride-pentafluoropropylene fluororubber (VDF-PFP fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene fluororubber (VDF-PFP-TFE fluororubber), vinylidene fluoride-perfluoromethyl vinyl ether-tetrafluoroethylene fluororubber (VDF-PFMVE-TFE fluororubber), and vinylidene fluoride-chlorotrifluoroethylene fluororubber (VDF-CTFE fluororubber).

[0047] <Negative electrode>

[0048] The negative electrode 30 includes, for example, a negative electrode current collector 32 and a negative electrode active material layer 34 . The negative electrode active material layer 34 is formed on at least one surface of the negative electrode current collector 32 .

[0049] [Negative electrode current collector]

[0050] The negative electrode current collector 32 is, for example, a conductive plate material. The negative electrode current collector 32 can be the same as the positive electrode current collector 22 .

[0051] [Negative Electrode Active Material Layer]

[0052] Figure 2 This is a cross-sectional view of the negative electrode active material layer 34 of the first embodiment taken by a scanning electron microscope (SEM). The negative electrode active material layer 34 includes composite particles 1 formed by composite carbonaceous particles and silicon particles. A plurality of composite particles 1 are included in the negative electrode active material layer 34. The negative electrode active material layer 34 is an example of a negative electrode material. The composite particles 1 function as a negative electrode active material. In addition to the composite particles 1, the negative electrode active material layer 34 may also include a binder, a conductive additive, and the like.

[0053] Composite particles 1 include first composite particles 1A and second composite particles 1B. The silicon content of first composite particles 1A is 0.5 wt % to 5 wt %. A plurality of first composite particles 1A are present in negative electrode active material layer 34. The silicon content of second composite particles 1B is greater than that of first composite particles 1A. The silicon content of second composite particles 1B is 60 wt % to 70 wt %. A plurality of second composite particles 1B are present in negative electrode active material layer 34. Composite particles 1 may include composite particles other than first composite particles 1A and second composite particles 1B.

[0054] The silicon content of the composite particles 1 can be measured by energy dispersive X-ray spectroscopy (EDS) by irradiating the composite particles 1 confirmed in the cross-sectional SEM image with an electron beam. In addition, the weight ratio of the carbonaceous particles in the composite particles 1 can also be measured by high-frequency induction heating combustion-infrared absorption method, etc., and the weight ratio of the silicon particles in the composite particles 1 can also be measured by ICP (inductively coupled plasma) emission spectrometry, etc.

[0055] The average silicon content of the composite particles 1 is, for example, 40% to 60% by weight, and preferably 45% to 50% by weight. The average silicon content of the composite particles 1 is, for example, an average value of at least 50 composite particles 1 .

[0056] In the negative electrode active material layer 34, the proportion of the first composite particles 1A is, for example, 3% by volume to 40% by volume, preferably 6% by volume to 30% by volume. In the negative electrode active material layer 34, the proportion of the second composite particles 1B is, for example, 1% by volume to 20% by volume, preferably 2% by volume to 15% by volume. For example, when a graph is formed with the silicon content of the composite particles 1 contained in the negative electrode active material layer 34 as the horizontal axis and the number of composite particles 1 having a silicon content within a predetermined range as the vertical axis, the graph has two peaks in the range of 0.5% by weight to 5% by weight and in the range of 60% by weight to 70% by weight.

[0057] The average secondary particle size of the composite particles 1 is 3 μm or more and 10 μm or less. If the average secondary particle size of the composite particles 1 is 3 μm or more, the conductivity between the composite particles 1 can be ensured even if the binder and the conductive auxiliary agent are small. In addition, if the average secondary particle size of the composite particles 1 is 10 μm or less, the composite particles 1 are not easily damaged during the charge and discharge of the lithium ion secondary battery 100.

[0058] The average secondary particle size of the composite particles 1 is obtained, for example, from a cross-sectional image of the negative electrode active material layer 34. The cross-sectional image can be measured using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). For example, the average secondary particle size of the composite particles 1 can be measured by observing the composite particles 1 at a magnification of 100,000 times using a scanning electron microscope JSM-7600 (manufactured by JEOL Ltd.) and performing image processing on the captured image.

[0059] For example, the average secondary particle size is obtained using image processing software HALCON (registered trademark, MVTec Software GmbH system). The software identifies the particles of the captured image, removes the particles that are not captured as a whole at the end of the observation field of view, measures the maximum length (diameter of the circumscribed circle of the particle) of each particle, and converts the particle size according to the maximum length. It is possible to obtain the quantitative reference cumulative particle size distribution by measuring 200 particles in this way, and thus calculate the average secondary particle size of the composite particle 1 and obtain.

[0060] The specific surface area of ​​the composite particle 1 is, for example, 3 m 2 / g above 25m 2 / g or less. The specific surface area can be measured, for example, by the BET method (multimolecular layer adsorption method). Specifically, it can be obtained by using Gemini 2360 (manufactured by Micromeritics) to pre-dry the sample at 200°C for 20 minutes under nitrogen flow, and then to flow nitrogen for 5 minutes, and then to obtain the specific surface area by the BET 7-point method using nitrogen adsorption.

[0061] A sufficiently large specific surface area of ​​the composite particles 1 means that there are a large number of gaps in the composite particles 1. The gaps between the composite particles 1 relieve stress concentration caused by expansion and contraction of silicon particles during charge and discharge, thereby preventing damage to the composite particles 1. In addition, by not excessively increasing the specific surface area of ​​the composite particles 1, it is possible to suppress excessive side reactions between the silicon particles of the composite particles 1 and the electrolyte.

[0062] Figure 3 Schematic diagram of composite particles 1 included in the negative electrode material of the first embodiment. Composite particles 1 are formed by composite carbonaceous particles 2 and silicon particles 3. First composite particles 1A and second composite particles 1B contain carbonaceous particles 2 and silicon particles 3, respectively. The abundance ratio of silicon particles 3 in the first composite particles 1A is lower than the abundance ratio of silicon particles 3 in the second composite particles 1B.

[0063] Both the carbonaceous particles 2 and the silicon particles 3 are amorphous. Here, amorphous refers to a structure that does not have a regular arrangement of atoms at a long distance on the scale of the interatomic distance, and is a substance that does not show a clear X-ray diffraction pattern. Not showing a clear X-ray diffraction pattern means, for example, that there is no peak with a half-peak width of 5° or less in the X-ray diffraction spectrum.

[0064] The amorphous carbonaceous particles 2 and silicon particles 3 have no anisotropy in the direction of lithium ion penetration during lithium ion insertion and extraction, and have excellent input-output characteristics. In addition, the amorphous silicon particles are not easily damaged during volume expansion.

[0065] The silicon particles 3 are not limited to simple silicon, but may be silicon alloys or silicon oxides. The silicon particles 3 may be crystalline or amorphous.

[0066] Silicon alloys such as X n Si represents. X represents a cation. X is, for example, Ba, Mg, Al, Zn, Sn, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Y, Zr, Nb, Mo, W, Au, Ti, Na, K, etc. n satisfies 0≤n≤0.5.

[0067] Silicon oxides such as SiO x It indicates that x satisfies, for example, 0.8≤x≤2. Silicon oxide may be composed of SiO2 alone, or may be composed of SiO alone, or may be a mixture of SiO and SiO2. In addition, part of oxygen in silicon oxide may be missing.

[0068] The average primary particle size of the silicon particles 3 is, for example, 1 nm or more and 50 nm or less. The average primary particle size of the silicon particles 3 can be obtained by the same method as the average secondary particle size of the composite particles 1. For example, by observing the cross section of the composite particles 1 using a scanning electron microscope JSM-7600 (manufactured by JEOL Ltd.), and performing image processing on the captured image, the average primary particle size of the silicon particles 3 can be measured. At this time, the carbonaceous particles 2 are removed by image processing, and the average primary particle size is calculated.

[0069] When the average primary particle size of the silicon particles 3 is within the above range, the decomposition of the electrolyte, which is one of the side reactions caused by the contact between the silicon particles 3 and the electrolyte, and the increase in the film resistance of the film formed therewith can be suppressed. In addition, when the average primary particle size of the silicon particles 3 is within the above range, the silicon particles 3 are not easily damaged due to expansion and contraction during charge and discharge.

[0070] The carbonaceous particles 2 are composited with the silicon particles 3. The carbonaceous particles 2 are, for example, graphite, graphene, carbides produced by firing pitch, carbides produced by firing resin, etc. The carbonaceous particles 2 may be two or more types.

[0071] Asphalts can also be coal-based asphalts, petroleum-based asphalts, and synthetic asphalts, such as coal tar, tar light oil, tar medium oil, tar heavy oil, naphthalene oil, anthracene oil, coal tar pitch, asphalt oil, mesophase pitch, oxygen-crosslinked petroleum asphalt, heavy oil, coke, low molecular weight heavy oil, and their derivatives.

[0072] Resins include thermoplastic resins such as polyvinyl alcohol, phenolic resins, epoxy resins, melamine resins, urea resins, aniline resins, cyanate resins, furan resins, ketone resins, unsaturated polyester resins, polyurethane resins, and modified products thereof. Phenolic resins include novolac-type phenolic resins and resol-type phenolic resins. Epoxy resins include bisphenol-type epoxy resins and novolac-type epoxy resins. Resins include polyethylene, polystyrene, acrylonitrile-styrene (AS) resins, acrylonitrile-butadiene-styrene (ABS) resins, polypropylene, polyethylene terephthalate, polycarbonate, polyacetal, polyphenylene ether, polybutylene terephthalate, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyvinyl chloride, and the like.

[0073] The conductive additive and the binder can use the same materials as those of the positive electrode 20. The binder in the negative electrode 30 may be, for example, cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, polyamide-imide resin, acrylic resin, etc., in addition to the materials mentioned in the positive electrode 20. Cellulose may be, for example, carboxymethyl cellulose (CMC).

[0074] <Diaphragm>

[0075] The separator 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The separator 10 isolates the positive electrode 20 and the negative electrode 30 to prevent a short circuit between the positive electrode 20 and the negative electrode 30. The separator 10 is spread in a plane along the positive electrode 20 and the negative electrode 30. Lithium ions can pass through the separator 10.

[0076] The diaphragm 10 has, for example, an electrically insulating porous structure. The diaphragm 10 is, for example, a single layer or a laminate of a polyolefin film. The diaphragm 10 may also be a stretched film of a mixture of polyethylene or polypropylene. The diaphragm 10 may also be a fiber nonwoven fabric composed of at least one constituent material selected from cellulose, polyester, polyacrylonitrile, polyamide, polyethylene and polypropylene. The diaphragm 10 may also be, for example, a solid electrolyte. Solid electrolytes include, for example, polymer solid electrolytes, oxide-based solid electrolytes, and sulfide-based solid electrolytes. The diaphragm 10 may also be an inorganic coating diaphragm. The inorganic coating diaphragm is formed by coating the surface of the above-mentioned film with a mixture of a resin such as PVDF or CMC and an inorganic substance such as alumina or silica. The inorganic coating diaphragm has excellent heat resistance and inhibits the precipitation of transition metals dissolved from the positive electrode to the surface of the negative electrode.

[0077] <Electrolyte>

[0078] The electrolyte is sealed in the package 50 and permeates the power generation element 40. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte. The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolytic salt. The electrolytic salt is dissolved in the non-aqueous solvent.

[0079] The solvent is not particularly limited as long as it is a solvent generally used for lithium-ion secondary batteries. The solvent includes, for example, any one of a cyclic carbonate compound, a chain carbonate compound, a cyclic ester compound, and a chain ester compound. The solvent may also contain these mixed in any proportion. Cyclic carbonate compounds are, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, fluoroethylene carbonate, vinylene carbonate, etc. Chain carbonate compounds are, for example, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), etc. Cyclic ester compounds are, for example, γ-butyrolactone, etc. Chain ester compounds are, for example, propyl propionate, ethyl propionate, ethyl acetate, etc. The ratio of cyclic carbonate to chain carbonate in the non-aqueous solvent is preferably set to 1:9 to 1:1 by volume, for example.

[0080] The electrolytic salt is, for example, a lithium salt. The electrolyte is, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, LiN(FSO2)2, etc. The lithium salt can be used alone or in combination of two or more. From the viewpoint of the degree of ionization, the electrolyte preferably contains LiPF6. The degree of dissociation of the electrolytic salt at room temperature in the carbonate solvent is preferably 10% or more.

[0081] When LiPF6 is dissolved in a non-aqueous solvent, the concentration of the electrolyte in the non-aqueous electrolyte is preferably adjusted to 0.5 mol / L or more and 2.0 mol / L or less. When the concentration of the electrolyte is 0.5 mol / L or more, the conductivity of the non-aqueous electrolyte can be fully ensured, and sufficient capacity can be easily obtained during charge and discharge. In addition, by suppressing the concentration of the electrolyte within 2.0 mol / L, the viscosity of the non-aqueous electrolyte can be suppressed, the mobility of lithium ions can be fully ensured, and sufficient capacity can be easily obtained during charge and discharge.

[0082] When LiPF6 is mixed with other electrolytes, the lithium ion concentration in the non-aqueous electrolyte is preferably adjusted to be above 0.5 mol / L and below 2.0 mol / L, and the lithium ion concentration from LiPF6 is further preferably above 50 mol % of the total.

[0083] <Package>

[0084] The package 50 seals the power generation element 40 and the non-aqueous electrolyte in its interior. The package 50 prevents the non-aqueous electrolyte from leaking to the outside and preventing moisture from entering the lithium ion secondary battery 100 from the outside.

[0085] For example Figure 1As shown, the package 50 includes a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The package 50 is a metal laminate film in which the metal foil 52 is coated with a polymer film (resin layer 54) from both sides.

[0086] As the metal foil 52, for example, aluminum foil can be used. The resin layer 54 can utilize a polymer film such as polypropylene. The material constituting the resin layer 54 may be different on the inside and outside. For example, as the material of the outside, a polymer with a high melting point, such as polyethylene terephthalate (PET) and polyamide (PA), etc., can be used; as the material of the polymer film on the inside, polyethylene (PE) and polypropylene (PP) can be used.

[0087] <Terminal>

[0088] Terminals 62 and 60 are connected to the positive electrode 20 and the negative electrode 30, respectively. The terminal 62 connected to the positive electrode 20 is a positive terminal, and the terminal 60 connected to the negative electrode 30 is a negative terminal. The terminals 60 and 62 are responsible for electrical connection with the outside. The terminals 60 and 62 are formed of conductive materials such as aluminum, nickel, and copper. The connection method can be welding or screw fixing. In order to prevent short circuits, it is preferred to protect the terminals 60 and 62 with insulating tape.

[0089] "Method for producing lithium-ion secondary battery"

[0090] The negative electrode 30, the positive electrode 20, the separator 10, the electrolyte solution, and the package 50 are prepared separately and assembled to produce the lithium ion secondary battery 100. An example of a method for producing the lithium ion secondary battery 100 is described below.

[0091] The negative electrode 30 is produced, for example, by sequentially performing a slurry preparation step, an electrode coating step, a drying step, and a rolling step.

[0092] The slurry preparation step is a step of mixing the negative electrode active material, the binder, the conductive auxiliary agent, and the solvent to prepare the slurry.

[0093] First, a method for producing a negative electrode active material is described. The negative electrode active material is produced through a composite particle production step, a mixing step, a drying step, and a heat treatment step.

[0094] First, in the composite particle production step, silicon particles and a carbon source are mixed in an organic solvent. The weight ratio of silicon particles and carbonaceous particles in the composite particles can be adjusted according to the mixing ratio of silicon particles and carbon source. For example, first composite particles 1A having a silicon content of 0.5 wt % to 5 wt % and second composite particles 1B having a silicon content of 60 wt % to 70 wt % are produced.

[0095] For silicon particles, for example, a silicon ingot is crushed in multiple stages to set the average particle size to be greater than 1 nm and less than 50 nm. The silicon ingot is produced, for example, by quenching molten silicon. By quenching the molten metal such as silicon after melting, excessive crystallization of the silicon particles can be prevented, and the silicon particles can be made amorphous. The cooling rate is, for example, 10 3 K / s above 10 8 Below K / s.

[0096] The pulverization of silicon ingots can be performed, for example, by a ball mill or a medium mill. Examples of ball mills include planetary mills, vibrating ball mills, cone mills, and tube mills. Examples of medium mills include attritors, sand mills, annealing mills, and tower mills. The particle size of silicon particles can also be controlled using a sieve.

[0097] The method for producing silicon particles is not limited to this method. For example, silicon particles can also be produced by a spray method. The spray method is a method of producing microparticles by spraying molten metal after melting. The spray method includes a method of forming powder by spraying an inert gas (gas atomization method), a method of forming a powder by spraying a rotating disk, a method of forming powder by spraying high-pressure water (water atomization method), and a method of injecting a sprayed metal into a high-speed rotating water flow (atomization method).

[0098] In addition, the molten metal may be cooled by a gun method, a single roller method, or a double roller method. By using these methods, the cooling rate of the molten metal can be accelerated. The powder or ribbon produced by this method may be further crushed to adjust the average particle size. In addition, the obtained powder may be subjected to ball milling or the like to make the silicon particles amorphous.

[0099] The carbon source is graphite, graphene, asphalt, resin, etc. Asphalt and resin can use the above-mentioned asphalt and resin. The carbon source is preferably at least one selected from graphite, graphene, novolac type phenolic resin, resol type phenolic resin, coal-based asphalt, and petroleum-based asphalt. Two or more carbon sources can also be used.

[0100] The organic solvent is methanol, ethanol, tetrahydrofuran, etc. A dispersant may also be added to the organic solvent. By adding the dispersant, the carbonaceous particles and the silicon particles are uniformly composited. Such composite particles have excellent electronic conductivity and are not likely to cause side reactions with the electrolyte during charge and discharge.

[0101] Next, the mixture of silicon particles and carbon source in an organic solvent is dried. The organic solvent is removed from the mixture by drying to obtain a powder. The drying method is not particularly limited, and an example thereof is spray drying.

[0102] Next, the dried powder is subjected to heat treatment. The resin or resin composition serving as a carbon source is incompletely burned and carbonized by the heat treatment step, thereby forming carbonaceous particles. Thus, the silicon particles and the carbonaceous particles are composited.

[0103] The mixture is preferably heat treated at a heat treatment temperature of 350 to 1200°C. When the heat treatment temperature is low, the carbon source cannot be fully carbonized, which may cause lithium capture during charging and discharging. When lithium is captured, the initial efficiency of the lithium-ion secondary battery decreases. When the heat treatment temperature is high, silicon particles and carbonaceous particles react to generate excessive amounts of silicon carbide. Silicon carbide is less helpful for charging and discharging among silicon compounds, and the conductivity of lithium ions is reduced, which is the reason for the reduction in the discharge capacity of the lithium-ion secondary battery.

[0104] The heat treatment time is preferably 1 hour to 72 hours. The heat treatment atmosphere is preferably a reducing atmosphere such as a nitrogen atmosphere or an argon atmosphere.

[0105] Next, a slurry is prepared using the composite particles prepared in the above order. The slurry can be prepared by mixing the first composite particles, the second composite particles, a binder, a conductive additive, and a solvent. The solvent is, for example, water, N-methyl-2-pyrrolidone, etc. By adjusting the mixing ratio of the first composite particles 1A and the second composite particles 1B in the slurry, the volume ratio of the first composite particles 1A and the second composite particles 1B in the negative electrode active material layer 34 can be adjusted.

[0106] The electrode coating step is a step of coating the slurry on the surface of the negative electrode current collector 32. The method for coating the slurry is not particularly limited. For example, a slit die coating method or a doctor blade method can be used as the slurry coating method. The slurry is coated at room temperature, for example.

[0107] The drying step is a step of removing the solvent from the slurry. For example, the negative electrode current collector 32 coated with the slurry is dried under a temperature environment of 80° C. to 350° C.

[0108] The rolling process is performed as needed. The rolling process is a process of applying pressure to the negative electrode active material layer 34 to adjust the density of the negative electrode active material layer 34. The rolling process is performed using, for example, a roll press device. The linear pressure of the roll press is, for example, 100 kgf / cm to 2500 kgf / cm.

[0109] The positive electrode 20 can be produced by the same procedure as the negative electrode 30. Commercially available products can be used for the separator 10 and the package 50.

[0110] Next, the positive electrode 20 and the negative electrode 30 are stacked so that the separator 10 is located between them to produce the power generation element 40. For example, the positive electrode 20, the separator 10, and the negative electrode 30 are stacked and pressed so that they are closely attached. When the power generation element 40 is a wound body, the positive electrode 20, the negative electrode 30, and the separator 10 are wound with one end side of the positive electrode 20, the negative electrode 30, and the separator 10 as the axis.

[0111] Finally, the power generation element 40 is sealed in the package 50. The non-aqueous electrolyte is injected into the package 50. After the non-aqueous electrolyte is injected, the non-aqueous electrolyte is infiltrated into the power generation element 40 by reducing pressure, heating, etc. The package 50 is sealed by applying heat, etc., to obtain the lithium ion secondary battery 100. In addition, the power generation element 40 may be immersed in the electrolyte instead of injecting the electrolyte into the package 50. It is preferred to leave it to stand for 24 hours after injecting the electrolyte into the power generation element.

[0112] The lithium ion secondary battery 100 of the first embodiment has composite particles with different silicon contents. Since the first composite particles 1A have a small silicon content, the volume change of the lithium ion secondary battery 100 during charge and discharge is small. On the other hand, since the first composite particles 1A contain silicon, they have a function as an active material. That is, the first composite particles 1A have a function as an active material and also act as a buffer material for the volume change of other composite particles. In addition, since the second composite particles 1B have a large silicon content, the discharge capacity of the negative electrode 30 is improved. By having composite particles with different characteristics in the negative electrode active material layer 34, the advantages of each composite particle are obtained. In addition, when the second composite particles 1B expand in volume, the first composite particles 1A serve as a buffer material, which can suppress the breakage of the composite particles 1 and suppress the reduction of the cycle characteristics of the lithium ion secondary battery 100. In addition, when the composite particles 1 expand in volume, the first composite particles 1A serve as a buffer material, and the composite particles 1 are closely attached to each other, so that the conductive path between the composite particles 1 becomes smooth.

[0113] Although the embodiments of the present invention have been described in detail with reference to the drawings, each structure of each embodiment and their combination are merely examples, and addition, omission, replacement, and other changes to the structure may be made without departing from the spirit of the present invention.

[0114] Example

[0115] "Example 1"

[0116] (Preparation of negative electrode active material)

[0117] <Production of the first composite particle>

[0118] Silicon (manufactured by Aldrich, purity 99% or more) was melted in a vacuum using an arc melting device. The molten metal was then blown onto a rotating copper roller using argon gas to rapidly cool the molten metal, producing silicon powder. The molten metal was then milled in an argon atmosphere using a planetary ball mill. Silicon nitride balls were made into silicon powder and pulverized for 24 hours to produce silicon particles with an average primary particle size of 5 nm.

[0119] Next, add 5 g of silicon particles and 200 g of tetrahydrofuran (Kanto Chemical Co., Ltd., special grade) to a 500 ml beaker and stir with a magnetic stirrer. Next, add 6.5 g of phenolic resin (DIC Co., Ltd.) and continue stirring for about 0.5 hours. Next, add 180 g of furan resin and continue stirring for 3 hours. Then, use a homogenizer to treat for 1 hour. Use an oven to heat treat the obtained mixture at 90°C for about 24 hours and then crush it to obtain a powder.

[0120] Next, 10.00 g of the powder was placed in an alumina crucible, and the temperature was raised from room temperature to 900° C. over 5 hours in an argon atmosphere, and heat treated at 900° C. for 4 hours, thereby producing first composite particles.

[0121] <Production of Second Composite Particles>

[0122] The second composite particles were prepared in the same procedure as the first composite particles. The method for preparing the second composite particles differed from the method for preparing the first composite particles in the mixing ratio of the silicon particles, the phenolic resin, and the furan resin.

[0123] <Production of other composite particles>

[0124] The other composite particles were prepared in the same procedure as the first composite particles. In the method for preparing the other composite particles, the mixing ratio of the silicon particles, the phenolic resin and the furan resin was different from that in the method for preparing the first composite particles.

[0125] <Measurement of the weight ratio of carbon content to silicon particles>

[0126] The weight ratio of carbonaceous particles to silicon particles in each of the first composite particle and the second composite particle was obtained using high-frequency induction heating combustion-infrared absorption method and ICP (inductively coupled plasma) emission spectrometry. First, the weight of the carbonaceous particles contained in the first composite particle and the second composite particle was obtained by high-frequency induction heating combustion-infrared absorption method. Next, the weight of the silicon particles contained in the first composite particle and the second composite particle was measured by ICP (inductively coupled plasma) emission spectrometry.

[0127] <Measurement of specific surface area of ​​composite particles>

[0128] The specific surface area of ​​the composite particles was determined using Gemini 2360 (manufactured by Micromeritics). The sample was pre-dried at 200°C for 20 minutes under a nitrogen flow, and nitrogen was further flowed for 5 minutes before the specific surface area was determined by the BET 7-point method based on nitrogen adsorption.

[0129] [Production of Evaluation Batteries]

[0130] A mixture of the first composite particles, the second composite particles, other composite particles, a binder, i.e., polyimide (PI), and acetylene black is dispersed in N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a slurry. The slurry is prepared in such a way that the weight ratio of the composite particles, acetylene black, and polyimide in the slurry is 80:10:10. In addition, the mixing ratio of the first composite particles and the second composite particles is adjusted in such a way that the volume ratio of the first composite particles and the second composite particles in the negative electrode active material layer is a predetermined ratio. The slurry is applied to a collector, i.e., copper foil, and rolled after drying to prepare an electrode (negative electrode) having a negative electrode active material layer formed thereon of Example 1.

[0131] Next, a separator composed of a polyethylene microporous film was sandwiched between the produced negative electrode and the Li foil as the counter electrode to obtain a laminate (power generation element). The laminate was placed in an aluminum laminate packaging bag, in which an electrolyte solution was mixed in a volume ratio of FEC:VC:EMC=1:1:8, and a mixed solution in which LiPF6 was dissolved in a concentration of 1.3 mol / L was injected, and then vacuum-sealed to produce a battery for evaluation of Example 1.

[0132] Next, the discharge capacity and cycle characteristics of the evaluation battery were obtained. The charge capacity was measured in a 25°C thermostat with a charge rate of 0.1C (the current value at which the discharge is completed within 10 hours when the constant current discharge is performed at 25°C), and then the initial discharge capacity was measured in a 25°C thermostat with a discharge rate of 0.1C to obtain the discharge capacity.

[0133] In addition, using the battery cell after the initial discharge capacity measurement, the 0.5C charge / 1C discharge is repeated 50 cycles in the above-mentioned charge and discharge order to obtain the cycle characteristics. The charge and discharge are performed in a constant temperature chamber at 45°C. The initial discharge capacity is set to 100%, and the value of the discharge capacity after 50 cycles is set to the cycle characteristics. The larger the initial discharge capacity and the cycle characteristics, the better.

[0134] "Examples 2 to 8"

[0135] In Examples 2 to 8, the mixing ratio of the first composite particles and the second composite particles when preparing the negative electrode slurry was changed, and the volume ratio of the first composite particles and the volume ratio of the second composite particles in the negative electrode active material layer were changed. In Examples 2 to 8, the same procedures as in Example 1 were also performed, and the same evaluations as in Example 1 were performed.

[0136] "Examples 9 and 10"

[0137] In Examples 9 and 10, the volume ratio of the first composite particles, the volume ratio of the second composite particles, and the average secondary particle size of the composite particles in the negative electrode active material layer were changed by changing the mixing ratio of the first composite particles, the second composite particles, and the other composite particles when preparing the negative electrode slurry. In Examples 9 and 10, the same evaluation as in Example 1 was performed.

[0138] "Examples 11 to 14"

[0139] In Examples 11 to 14, the particle size of the silicon particles constituting the composite particles was changed. In Examples 11 and 12, the particle size of the silicon particles was different from that of Example 5. In Examples 13 and 14, the particle size of the silicon particles was different from that of Example 6. In Examples 11 to 14, the same procedures as in Example 1 were followed and the same evaluations as in Example 1 were performed.

[0140] "Examples 15 and 16"

[0141] Examples 15 and 16 differ from Example 1 in that the average specific surface area of ​​the composite particles was changed. Examples 15 and 16 were also carried out in the same manner as in Example 1, and the same evaluations as in Example 1 were performed.

[0142] "Comparative Examples 1 and 2"

[0143] In Comparative Examples 1 and 2, the particle size of the silicon particles constituting the composite particles was changed. In addition, the mixing ratio of the first composite particles and the second composite particles when preparing the negative electrode slurry was changed, and the volume ratio of the first composite particles and the volume ratio of the second composite particles in the negative electrode active material layer were also changed. In Comparative Examples 1 and 2, the same procedures as in Example 1 were also performed, and the same evaluations as in Example 1 were performed.

[0144] "Comparative Examples 3 to 5"

[0145] In Comparative Examples 3 to 5, neither the first composite particles nor the second composite particles were added when preparing the negative electrode slurry. Comparative Examples 3 to 5 were also carried out in the same manner as in Example 1, and the same evaluations as in Example 1 were performed.

[0146] "Comparative Examples 6 to 8"

[0147] In Comparative Examples 6 to 8, a crystalline material was used as either the silicon particles or the carbonaceous material constituting the composite particles. In Comparative Examples 6 to 8, the same procedures as in Example 1 were followed and the same evaluations as in Example 1 were performed.

[0148] Tables 1 and 2 show the evaluation results of Examples 1 to 18 and Comparative Examples 1 to 8.

[0149] [Table 1]

[0150]

[0151] [Table 2]

[0152]

[0153] Explanation of symbols:

[0154] 1…composite particles, 1A…first composite particles, 1B…second composite particles, 2…carbonaceous material, 3…silicon particles, 10…separator, 20…positive electrode, 22…positive electrode current collector, 24…positive electrode active material layer, 30…negative electrode, 32…negative electrode current collector, 34…negative electrode active material layer, 40…power generating element, 50…package, 52…metal foil, 54…resin layer, 60, 62…terminals, 100…lithium ion secondary battery.

Claims

1. A negative electrode material for a lithium ion secondary battery, wherein: Composite particles containing amorphous carbonaceous particles and amorphous silicon particles. The average primary particle size of the silicon particles is not less than 1 nm and not more than 50 nm, The composite particles include first composite particles having a silicon content of 0.5 wt % to 5 wt % and second composite particles having a silicon content of 60 wt % to 70 wt %.

2. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The ratio of the first composite particles is 3 volume % to 40 volume %, and the ratio of the second composite particles is 1 volume % to 20 volume %.

3. The negative electrode material for lithium ion secondary battery according to claim 2, wherein The ratio of the first composite particles is 6 volume % to 30 volume %, and the ratio of the second composite particles is 2 volume % to 15 volume %.

4. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The average secondary particle size of the composite particles is 3 μm or more and 10 μm or less.

5. The negative electrode material for lithium ion secondary battery according to claim 1, wherein The specific surface area of ​​the composite particles is 3m 2 / g above 25m 2 / g or less.

6. A negative electrode for a lithium ion secondary battery, in, The negative electrode material for a lithium ion secondary battery according to claim 1 is included.

7. A lithium ion secondary battery, wherein: The invention comprises the negative electrode for lithium ion secondary battery according to claim 6, a positive electrode, and an electrolyte.

Citation Information

Patent Citations

  • Negative electrode material for lithium secondary battery, its manufacturing method, negative electrode for lithium secondary battery using the negative electrode material, and lithium secondary battery

    JP2008277232A